The Relationships among Leadership, Entrepreneurial Mindset, Innovation and Competitive Advantage (A Conceptual Model of Logistics Service Industry) - Sudrajat, Darjat (Binus Business Review, 2015)
Nowadays, improvement of competitive advantage is an important and urgent issue facing logistics service companies in Indonesia. Some previous researches showed that to improve the competitive advantage could be conducted through improvement of leadership, entrepreneurial mindset and innovation variables. This research intended to recognize relationships among the variables. The research used causal-explanatory method. The results of research encompass a conceptual model, status of each variable and hypotheses. The conceptual model could be further verified through verification research.